Applications of constructive developmental theory to the studies of leadership development : a systematic review - Florio, Linda (Cranfield University, 2008)
Purpose. The purpose of this dissertation is to present three main outcomes of the systematic review undertaken: - A synthesis of extant literature on leadership development from the angle of constructive developmental theory. - A review of the two approaches in constructive developmental theory most widely used in conjunction with studies of leadership development. - An integrative framework of the process and context of leadership development from the constructive developmental perspective. In exploring the directions of further inquiry, the framework is applied to the development of a transformational style of leadership in the settings of executive leadership development initiatives. Cont/d.